Status of Primary Market Response in Nepal (Journal of Nepalese Business Studies, 2018)
This paper attempts to analyze the status of primary market response in Nepal using secondary data collected from annual reports of various capital market institutions of 22 years starting from 1993/94 to 2014/15. This paper follows descriptive research design and analysis has been carried out throughout accordingly. The study concludes that the total capital mobilization has been increasing during the study period implying there is transfer of capital from surplus sectors to the productive investments gradually. Ordinary shares including rights offerings has found more active in the primary market than that of other alternative market mechanisms. It means preference shares, debentures, mutual funds and citizen unit schemes have been found still unorganized in Nepal. initial public offerings is mainly dominated by the ordinary shares has been highly oversubscribed during the study period except in few cases. This particular case shows the public response towards primary market is found good. However, when we go through all other indicators the primary market has still found unsystematic, vulnerable and even small in size. There are a very limited number of merchant bankers as financial intermediary in the primary market. The liberalization policy has brought major changes in regulatory and institutional framework but the primary market has yet to be improved and advanced so that the corporate houses can benefit by designing optimum capital structure and investors are also benefitted by developing appropriate investment portfolios. More specifically, the primary market more dynamic ofter the introduction of federal republic system since 2006/07 in Nepal, though it is still unstable.The Journal of Nepalese Business Studies Vol. X No. 1 December 2017, Page: 56-68